IMPLEMENTATION OF VIENNA RECTIFIER WITH SLIDING MODE CONTROL FOR ELECTRIC VEHICLE CHARGING STATIONS (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2024)
This work recommends using an electric vehicle (EV) charging station employing a Vienna rectifier (VR) with sliding mode control. The Vienna rectifier is preferred for high-power applications due to its reduced harmonic distortion and improved power factor correction. Sliding mode control is used to regulate the rectifier's output voltage and current, allowing for reliable and efficient charging of EVs. The suggested system is modeled, and the simulation outcomes are presented to demonstrate the value of the recommended approach concerning stability, strength, and unexpected responsiveness. The proposed technology is expected to contribute to developing more dependable and effective EV charging stations.
Keywords: Electric vehicle; Charging station; Sliding mode control (SMC); Power factor; Harmonics